Does Health Education Prevent Dermatitis Wounds in Teenagers? - Nursasmita, Rizqi; Yuliani, Nadia; Hidayat, Rizki (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Dermatitis accounts for 97% of the 389 skin disease cases in Indonesia, which often occur in teenagers. They suffer from dermatitis, which can include intense itching and scratching accompanied by skin hypersensitivity. Scratching can cause several skin conditions, including blemishes and erythematous, excoriated, and crusting lesions that compromise the skin and increase the chance of secondary infection and spreading to the deeper layers of the skin (cellulitis) or forming pockets of pus. Objective: This study aims to determine the effect of health education on knowledge, attitudes, and behavior for preventing dermatitis wounds at the Ciracas Village Community Health Center, Jakarta, Indonesia. Method: A quasi-experimental study, pre-test, and post-test were approached. In this study, research subjects were given a questionnaire pre-test before intervention (health education using a booklet). After that, a questionnaire post-test will be given to see the final results of the intervention. The sampling technique was carried out using purposive sampling with 33 respondents. The statistical tests used were univariate and bivariate, using a paired sample t-test. Result: The results showed that there were differences in the results of the pre-test and post-test with a p-value of 0.000. There are changes in knowledge, attitudes, and behavior. Conclusion: Health promotion with booklet media influences knowledge, attitude, and behavior. Recommendation: It is hoped that information regarding the prevention of dermatitis wounds can be combined with another preventive method